Rancang Bangun Sistem Palang Pintu Otomatis Berbasis Arduino Uno Dengan Teknologi RFID - Dawasoka, Siti Milda Alkan; Kautsar, M. Dimas; Firizki, Muh; Rahman, Abdul (Universitas Multi Data Palembang, 2025)
This research develops a prototype of an automatic gate barrier system based on Arduino Uno by implementing RFID technology. The system is designed to improve the efficiency of entry and exit access in parking areas, reduce vehicle queues, and provide greater convenience for users. It utilizes RFID technology to identify registered cards and automatically open the gate barrier if a valid card is detected. Additionally, the system is equipped with an infrared sensor to detect vehicles that have passed through the barrier. The automatic gate barrier system employs an Arduino Uno microcontroller as the central control unit for the entire system. This system is expected to address common issues encountered in manual parking systems. The testing results of the automatic gate barrier system include RFID tag reading capability, registered RFID verification, the distance between the RFID card and the RFID reader, as well as the infrared sensor functionality, all of which demonstrate that the system operates effectively.